Cyprus, Sardinia and Sicily: A Maritime Perspective on Interaction, Connectivity and Imagination in Mediterranean Prehistory. Issue 1 (February 2022) - Knapp, A. Bernard; Russell, Anthony; van Dommelen, Peter
Abstract : In this study, we outline a maritime perspective on interaction in the Late Bronze/early Iron Age Mediterranean. In response to what has elsewhere been termed the 'maximalist' approach, which foregrounds direct, long-distance trading connections between distant Mediterranean regions as a key feature of Late Bronze Age exchange systems, we propose a more nuanced, 'minimalist' and argue that notions of contact, connectivity and mobility need to be carefully distinguished if we wish to discuss both the material and social dimensions of maritime mobility. In particular, we critique the prominently proposed, allegedly direct trade route between Sardinia and Cyprus. The network we suggest hinges on multiply connected nodes, where a variety of social actors take part in the creation and maintenance of maritime connections. By unpacking several such nodes between Sardinia and Cyprus, we demonstrate that simply asserting the dominance of Sardinian, Cypriot or Aegean mariners falls short of the complex archaeological evidence and eschews possible social interpretations. In conclusion, we submit that maritime connectivity is an inherently social activity, and that a culturally diverse prehistoric Mediterranean was connected by multiple interlocking and overlapping networks.